Using Microsoft Office 2013 With Windows 8 - Wilson, Kevin; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2014)
Learn Office the easy way, no jargon. Clear, concise and to the point. Using Office 2013 is the essential step by step guide to getting the most out of Microsoft Office traditional application (not SharePoint), providing a resource for both the beginner and the enthusiast. This book explores constructing professional looking documents; adding and using graphics and clipart; fonts, tables, graphs and formatting; creating stunning PowerPoint presentations for your lessons, lectures, speeches or business presentations; PowerPoint animations and effects; setting up your projector and laptop ready to present; using Excel to create spreadsheets to analyse data; Excel functions and formulas; Excel charts and graphs; and more... Techniques are illustrated in step-by-step using photography and screen prints throughout, together with concise, easy to follow text from an established expert in the field, provide a comprehensive guide to office applications. Whether you are new to Microsoft Office, an experienced user or studying a computer skills course this book will provide you with a firm grasp of the underpinning foundations and equip you with the skills needed to use Office.
Keywords: Computer science; Computer Science; Computer Science, general; Electronic books